The story of the Brethren movement - Veitch, Thomas Stewart, 1874-1938 (London, UK Pickering and Inglis)
Includes photographs.
Copy 1 donated by Mrs Dunlop. Copy 2 donated by Dr L.L. Edwards.
Keywords: Brethren movement -- history